EFEKTIVITAS AKUPRESUR TITIK HEGU (LI4) TERHADAP INTENSITAS NYERI DISMENOREA PADA REMAJA PUTRI DI PRAKTEK MANDIRI BIDAN (PMB) ANIK SRI WILUJENG - Xyqha Qoulan Tsaqila Muchtar; Raden Maria Veronika Widiatrilupi (Journal of Innovative and Creativity (Joecy), 2026)
Dysmenorrhea frequently impairs daily functioning among adolescent females, thus necessitating non-pharmacological approaches such as acupressure applied to the Hegu (LI4) acupoint. The objective of this research was to assess the efficacy of LI4 acupressure in alleviating dysmenorrheic pain severity in adolescent girls receiving care at Anik Sri Wilujeng's Independent Midwife Practice (PMB). A pre-experimental one-group pretest-posttest design was employed, involving 32 participants who were recruited through purposive sampling. Pain levels were evaluated using the Numeric Rating Scale (NRS) both prior to and following the LI4 acupressure procedure. Data analysis was performed using the Wilcoxon Signed Rank Test. Prior to the intervention, the majority of participants reported severe pain (40.6%), whereas following the intervention, most participants experienced no pain (53.1%). Pain reduction was observed in 27 respondents, 5 respondents exhibited no change, and none reported an increase in pain. The Wilcoxon test revealed a statistically significant difference between pretest and posttest scores (p = 0.000).